Enzyme complex supplementation in different nutrient levels diets on pigs feces excretion and anaerobic digestion - Ruiz, Urbano dos Santos; Thomaz, Maria Cristina [UNESP]; Lucas Junior, Jorge de [UNESP]; Fonseca Pascoal, Leonardo Augusto; Watanabe, Pedro Henrique; Amorim, Alessandro Borges; Neves Xavier, Cristiane de Almeida; Silva, Adriane Andrade (Univ Sao Paolo, 2017)
This research aimed to evaluate enzyme supplementation in diets with different nutritional levels for pigs in their feces excretion and anaerobic digestion. Fifty four gilts were placed on diets formulated to achieve 100 or 95 or 90 % of a pig's nutrient requirements, with the addition of an enzyme complex containing amylase, beta-glucanase, cellulase, pectinase, xylanase, protease and phytase (diets 100E, 95E and 90E) or without the enzymes (diets 100, 95 and 90). The trial was divided into three periods (1, 1-2 and 1-3) based on the animal weight. The enzyme complex reduced (p < 0.05) excretions per period and per unit of weight gain (residue coefficients) of organic matter (OM) in Period 1, of N, Ca, Zn and Na in Period 1-2, and of Na excretions and residue coefficients in Period 1-3. Animals fed diet 95E had lower excretions (p < 0.05) of dry (DM), organic and mineral matters, N, Ca, Fe, Mn and Cu, and lower residue coefficients (p < 0.05) of DM, OM, P, Fe, Mn and Cu compared with the animals fed diet 95, in Period 1-3. Numerically, the enzyme complex improved biogas and methane production potentials in anaerobic digestion of the feces. The use of an enzyme complex in a diet formulated to provide 95 % of the gilts' nutrient requirements reduced fecal excretion and positively affected the anaerobic digestion of feces. These data show that pig nutrition and feeding are important tools for reducing the potential environmental impact of pig production.
Keywords: biogas; environmental impact; fecal production; swine